Effect of calibration of a medical review monitor on the visibility of mandibular canal at dental implant sites: A cone beam CT study - Mustafa Alkhader; Malik Hudieb; Khalid Kheirallah (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of this study was to assess the visibility of mandibular canal (MC) on cone beam CT (CBCT) images using a medical review monitor under two different calibration modes. The effect of age, gender, and location of the dental implant site was also assessed. Materials and Methods: CBCT images of 428 dental implant sites were selected for the study. Images were displayed twice on a medical review monitor using two different calibration modes: standard and DICOM, and two observers evaluated the visibility of the MC using four-point scoring scale (1-4, poor to excellent). Cohen Kappa was used to assess intra and inter-rater reliability. Chi-square test was used to compare proportions of MC visibility by gender and location and one-way ANOVA was used to compare mean age and MC visibility. Results: Each observer classified the visibility of MC with a total agreement of 100% between DICOM mode and standard mode (Kappa = 1, P < 0.001 for each observer). In each mode, a strong agreement (inter-rater reliability) was detected between the observers (Cohen's kappa = 0.88 for both modes, P < 0.001) with a percent agreement of 95.3% for each mode. Gender and location were not statistically associated with MC visibility (P > 0.05). Age, however, was a significant predictor of MC visibility (P < 0.05). Conclusions: DICOM calibration had no added value over standard calibration for assessing the visibility of MC at dental implant sites on a medical review monitor. Only the age had significant effect on the visibility.